Parameter optimization and active control of electromechanical suspension systems - Kuhnert, Willian Minnemann [UNESP]; Silveira, Marcos [UNESP]; Gonçalves, Paulo José Paupitz [UNESP] (Springer Nature, 2018)
This paper has as object of study a simplified model for the the automobile suspension system, which can become a regenerative system by coupling a RLC electric circuit to the mechanical system. The main objectives of this paper are to study and optimize a simplified electromechanical suspension model that, when in passive mode, harvests energy, while maintaining the handling stability and passenger comfort, and when in active mode, uses energy to improve comfort for passengers and handling stability with least effort. A multi-objective optimization procedure was carried out and Pareto frontier was obtained for the objective functions when considering the passive mode. When considering active control, changes were proposed to the optimal control in order to reduce control effort for feedforward strategy, while for feedback strategies, the stability gain range was obtained by Routh-Hurwitz criterion. The proposed control sets have particular advantages regarding isolation, energy harvested and control effort.
Keywords: Control; Electromechanical suspension; Energy harvesting; Optimization; Regenerative suspension